Rifampin-divalproex drug-drug interaction in an adult patient: A case report - Christine Doran, PharmD; Michael Moro, MEd; Jennifer Green, DO; Kristen N. Gardner, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
The divalproex (DVP) package insert states that rifampin may increase the oral clearance of valproate by 40% and that valproic acid derivative dose adjustments may be required when starting or stopping rifampin. However, the overall clinical significance of this drug-drug interaction remains unclear given that limited clinical outcome data has been published. This case describes a 52-year-old female with bipolar disorder, borderline personality disorder, and PTSD who was previously stable on a medication regimen consisting of DVP delayed-release 500 mg every morning and 1500 mg every evening (baseline steady-state trough 99.8 mcg/mL). Throughout rifampin therapy for latent tuberculosis treatment, she required an increase in both the frequency of DVP administration, from 2 to 3 times daily, and DVP dose by 75% to maintain clinical stability. Valproic acid trough concentrations ranged from 56.4 to 75.9 mcg/mL during the 4-month course of rifampin. This report supports that the DVP-rifampin interaction may be clinically significant and of a greater magnitude than suggested by the package insert.